Diagnosis of Helicobacter pylori Infection Using ELISA for Detection of Serum IgM, IgG and IgA Antibodies - MH K. Ansari; Sh A.Yavari (Tehran University of Medical Sciences, 2007)
Background: Helicobacter pylori is gram negative bacteria and is the etiologic agent of some gastrointestinal disease are such as chronic gastritis, gastric ulcers, lymphoma and aden carcinoma. Multiple invasive and noninvasive methods for detection of this infection are available, and among non invasive methods diagnostic value of specific IgM, IgG and IgA by ELISAis one of the best methods. The aim of this study to detect H. pylori antibodies for IgM, IgG and IgA by ELISA method. Methods: Blood samples From 131 referred patients (78 female and 53 male) for detection of H.pylori was taken and serum separated for detection of IgM, IgG and IgA antibodies. IgG assessed by EIU units (42 was Positive) .Also for IgM and IgA antibodies reported by U/ml unit (12 was Positive). Results: 131 Samples were tested for H. pylori IgM, IgG and IgA antibodies and showed 27.47%, 42% and 25.19% positive for IgM, IgG and IgA antibodies respectively. Age group 20-40 years old for IgM, IgG and IgA antibodies 23.3% and 28.3% and 16.7% positive respectively and for 41-80 years old IgM, IgG and IgA antibodies were 31%, 53.5% and 32%, respectively. The above data showing infection is higher at 41- 80 years old patients. Conclusion: The simple method for detection of H. pylori antibodies are available commercially and have sensitivity and specificity for H. pylori diseases. IgG, IgM and IgA have diagnostic importance, therefore regarding acceptable sensitivity and specificity, ease of work with ELISA, being economical and non invasive, it can be employed in diagnosis of H. pylori infections.